Análise da proteína EGFR em carcinoma espinocelular de lábio - Strieder, Luciana Rocha [UNESP] (2015)
Lip squamous cell carcinoma (SCC) is one of the most common malignancies affecting especially lower lip due to sun exposure. This study aimed to evaluate three methods of histological grading (WHO, BD and MRH), analyze the expression of EGFR protein on the lip of SCC, compared with actinic cheilitis (AC) and correlates them with the prognosis. Data from 53 patients with lip SCC were collected for the clinicopathological and histological evaluation. 22 cases of SCC and 19 AC underwent immunohistochemical reaction with EGFR protein and analyzed by an automated analyzer for evaluation of protein expression. The average age was 65 years, 69,8% were men, lower lip was the site of predilection with 94,4% and 66,03% of patients were in early stages (T1 + T2). 52.83% and 64.15% cases respectively were graduates in low risk prognosis or grade 1 by BD and WHO scales, the MRH model graduated 54.72% cases as medium risk prognosis or grade 2. The simplest grading model and easy to apply in lip SCC was the BD scale and more efficient because when in high histological grade was associated with lower overall survival (P = 0.045). Overall survival was 87,8% at 5 years. Advanced clinical stage (T3 + T4) and lymph node involvement (N1) were associated with lower overall survival and recurrence-free survival (P = 0.002; 0.005; 0.007 and 0.01). Surgical treatment combined with radiotherapy was associated with lower recurrence-free survival (P = 0.03). The expression of EGFR protein had no statistically significant difference between AC and lip SCC. The lip SCC when in advanced stages and high histological grades, is associated with a worse prognosis, early diagnosis is essential for choosing the best treatment and survival of patients, avoiding mutilation and consequently, loss in quality of life.